Enhancing teacher performance: The impact of emotional support and work passion - Purwanto, Edy; Rahmawati, Dyah Ayu; Kiptiyah, Siti Maryatul (Edelweiss Applied Science and Technology, 2025)
The research aims to analyze the psychological factors affecting teachers in educational settings. Psychological factors are under-researched and therefore require further elaboration. In educational environments, multiple factors contribute to shaping teacher performance, which is closely related to student achievement. Among these, psychological dimensions such as emotional support, teacher work passion, and teacher engagement warrant closer examination in primary schools. Quantitative research methods are used to analyze the data, involving 172 teachers in the study. The findings highlight the significant influence of teacher work passion and emotional support on teacher engagement. Additionally, the results reveal that emotional support does not directly influence teacher performance, whereas teacher work passion does. This study emphasizes the importance for educational institutions and administrators to recognize and nurture these interconnected factors to establish effective teaching and learning environments.